Peningkatan Pengetahuan Kesiapsiagaan Bencana Dan Konsep Diri Terhadap Gempa Bumi Siswa - Ambia Nurdin; Chairummi Chairummi (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
Preparedness for disaster risk reduction is needed in the face of disaster, especially the children and elderly who are the most vulnerable age on the risk of casualties in a disaster. Until now, even the disaster is still happening. Therefore, disaster management paradigm aimed to reduce the impact or risk of such catastrophic disaster preparedness. Understanding of disaster mitigation at primary education is one of the solutions that need to be done in Indonesia. Prepare preparedness awareness of disaster risk reduction is important because the elementary school level students are at great risk in the event of disasters especially earthquakes. The purpose of this study was to describe the influence of self-concept and knowledge of students at SDN 27 and MIN Merduati Kuta Alam sub-district of Banda Aceh on disaster risk reduction preparedness earthquake. The research was conducted in the form of a cross sectional survey design. The population in this study were all students at SDN 27, as many as 223 and as many as 110 MIN Merduati Kuta Alam sub-district of Banda Aceh, the number of samples to be taken in this study were as many as 52 students at SDN 27 and 69 students in the MIN Merduati with stratified random sampling technique. Primary data collection method is a way to spread form questionnaire to students. Descriptive and analytical analysis with Spearman Rank Correlation coefficient by calculating the correlation coefficient. The results of knowledge in students MIN Merduati which shows that there is a correlation between the knowledge of the preparedness on students Merduati MIN (r = 0,284), knowledge on the students of SDN 27 (r = 0,210). Self-concept in students Merduati MIN is 0,792 which shows that the correlation between self-concept on student preparedness Merduati MIN (r = 0,032), self-concept in students of SDN 27 is (r = 0,165). The average value depending on the child's knowledge and preparedness MIN with mean difference (-1,174), the concept of child-MIN and preparedness with the average difference (6,493), the elementary school students with the knowledge and preparedness mean difference (-1,154), MIN child's self concept and preparedness with the average difference (6,212). The conclusion suggests that there is a relationship between children's knowledge and preparedness MIN with no knowledge of the relationship between elementary school children, elementary school children's self concept and MIN with disaster preparedness. And all the variables have a significant mean difference. There should be a study of the integration of disaster in the curriculum and the teacher's role is important in the formation of self-concept.